Processos de magnetização e magnetoimpedância em filmes com exchange bias - Silva, Ricardo Barreto da (2006)
In this work, the magnetization process and the magnetoimpedance effect in thin films with exchange bias were studied. We have investigated NiO/NiFe and NiFe/FeMn/Ta multilayer produced by magnetron sputtering on glass and Si(100) substrates, respectively. The exchange anisotropy in the NiO/NiFe samples were induced by a field cooling process, with a static magnetic field (2 kOe), from a temperature Tc > T > TN to the room temperature. In the NiFe/FeMn samples, the exchange anisotropy was induced during the deposition by application of a static magnetic field (460 Oe). The structural characterization was made by high angle x-ray diffraction in a q-2q setup and Cu-Ka radiation. The static magnetic characterization was performed by a VSM. The real and imaginary parts of the impedance were measured as a function of the current frequency (100kHz 1.8 GHz) and of the magnetic field intensity (± 300 Oe). The NiO multilayer was insensitive to the magnetoimpedance. The magnetoimpedance ratio was as large as 70 % in the NiFe/FeMn/Ta multilayer. On the other hand, the center of symmetry of the MI curves are shift of the position around H = 0 to H = Heb. The angular dependencies of the exchange bias field were calculated to prove the Mauri model to the exhange bias. The dispersion relation obtained by MI vs. f curves was fitting combined the Smit-Beljers approach to the FMR and mode s Mauri to the exchange bias. This fitting allowed that intrinsic parameters, such as the anisotropies of the system, were obtained. In summary, the MI and EB effects were grouped to origin a new magnetic system with singular magnetic characteristics. The MI curves are shift with respect to H = 0 and it allowed that the EB effect could be studied through the MI measurement.